Advances in Intelligent Information Hiding and Multimedia Signal Processing Proceedings of the Thirteenth International Conference on Intelligent Information Hiding and Multimedia Signal Processing, August, 12-15, 2017, Matsue, Shimane, Japan, Part I (Smart Innovation, Systems and Technologies,, 2018)
This volume includes papers presented at IIH-MSP 2017, the 13th International Conference on Intelligent Information Hiding and Multimedia Signal Processing, held on 12-15 August 2017 in Matsue, Shimane, Japan. The conference covered topics ranging from information hiding and security, and multimedia signal processing and networking, to bio-inspired multimedia technologies and systems. This volume focuses on subjects related to multimedia security and applications, wearable computing, Internet of Things (IoT) privacy and information security, biomedical system design and applications, emerging techniques and applications, soft computing and applications, applications of image encoding and rendering, and information hiding and its criteria. Updated with the latest research outcomes and findings, the papers presented appeal to researchers and students in the corresponding fields.